La biblioteca del convento de los dominicos de San Esteban de Salamanca en el siglo XVIII. - Vivas Moreno, Agustín (Revista General de Información y Documentación, 2000)
One of the best convent libraries for the number and quality of its book collection is analysed using MS 565 from tbe Salamanca University Library. A short introduction dealing with the importance of books aud reading to the Do minician Order at San Esteban is followed by a quantitative study of the books preserved, an analysis of the structure of the library. and an examination of the books according to place and language of publication. The library’s contents are analysed: first, religious books and then, those on other subjects. In con clusion, tbe library of the Convent of San Esteban at Salamanca is a faithful re presentative of Baroque culture, a true heritage for the study of scholasticism and its polemics, and confirms tbe introduction of modern thought in Spain.